2009
DOI: 10.1645/ge-1588.1
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscope Study of Ancient Parasite Eggs Recovered From Korean Mummies of the Joseon Dynasty

Abstract: We have previously shown that parasite eggs have been identified in the coprolites of Korean mummies. These eggs have shed light on parasitic infection patterns in Korean populations living several hundred years ago. We conducted a scanning electron microscopy (SEM) study on ancient Trichuris trichiura, Ascaris lumbricoides, Metagonimus yokogawai, Paragonimus westermani, and Gymnophalloides seoi eggs recovered from Korean mummies of the Joseon Dynasty. We anticipated that the taphonomic conditions of mummifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 30 publications
3
28
0
Order By: Relevance
“…The results of T. trichiura and A. lumbricoides are relevant to this study. Shin et al (2009) found that the eggs of T. trichiura were generally well preserved but that the mucoid polar plugs were often lost in mummified eggs. They found that archaeological A. lumbricoides eggs were broken or flattened and that the details of the mammillated coats were not well preserved.…”
Section: What Is Known About Parasite Egg Taphonomy and Recovery?mentioning
confidence: 96%
“…The results of T. trichiura and A. lumbricoides are relevant to this study. Shin et al (2009) found that the eggs of T. trichiura were generally well preserved but that the mucoid polar plugs were often lost in mummified eggs. They found that archaeological A. lumbricoides eggs were broken or flattened and that the details of the mammillated coats were not well preserved.…”
Section: What Is Known About Parasite Egg Taphonomy and Recovery?mentioning
confidence: 96%
“…), and the lung fluke (Paragonimus sp.). From Korea, a variety of researchers reported M. yokogawai, Paragonimus westermani, Gymnophalloides seoi and Taenia eggs f in mummies , Seo et al, 2009, Shin et al, 2009a, 2009b, 2011. Thus, food related parasites were very well established in Asia.…”
Section: R E I N H a R D E T A L I N I N T E R N At I O N A L J O Umentioning
confidence: 99%
“…The T. trichiura eggs were thin-walled and variously damaged or deformed in comparison to eggs of the same species recovered from mummies from other sites ( Aspöck et al, 1996;Martinson et al, 2003;Seo et al, 2007;Shin et al, 2009;Kumm et al, 2010). The polar plugs may not have been missing, but rather may not have yet been formed.…”
Section: Discussionmentioning
confidence: 79%
“…The preservation of eggs in mummies ranges from pristine (Kumm et al, 2010) to excellent (Seo et al, 2007;Shin et al, 2009), deformed (Reinhard and Urban, 2003) to degraded (Searcey et al, 2013). Some whipworm eggs documented by Kumm et al (2010) were fully embryonated which is unexpected in mummy contexts.…”
Section: Discussionmentioning
confidence: 99%